2022
DOI: 10.3389/fpls.2022.997475
|View full text |Cite
|
Sign up to set email alerts
|

Under cadmium stress, silicon has a defensive effect on the morphology, physiology, and anatomy of pea (Pisum sativum L.) plants

Abstract: Soil pollution with cadmium (Cd) is a serious threat to plant growth and development. On the other hand, silicon (Si) can support plants to cope with Cd stress. However, the Cd stress mitigating impact of Si reduction in pea (Pisum sativum L.) is not known. The objective of this study is to see if and how Si can reduce Cd toxicity. To the end, a greenhouse pot experiment was performed twice during the 2018/2019 and 2019/2020 seasons to investigate the effect of Si on the growth, anatomy, and biochemistry of Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…[30] found reduced seedling weight when they [31] also reported decreased root and shoot dry weight in peas upon Cd application. In line with our findings, Cd also reduced the growth of other plant species [32][33][34][35]. In this regard, Cd stress inhibits root and stem cell growth by inhibiting cell elongation and cell division via an inhibition activity of the glycolysis pathway.…”
Section: Discussionsupporting
confidence: 91%
“…[30] found reduced seedling weight when they [31] also reported decreased root and shoot dry weight in peas upon Cd application. In line with our findings, Cd also reduced the growth of other plant species [32][33][34][35]. In this regard, Cd stress inhibits root and stem cell growth by inhibiting cell elongation and cell division via an inhibition activity of the glycolysis pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported that humic acid and silicon improve plant growth, providing resistance against abiotic stress and reducing heavy metal stress [22,[55][56][57]. Kim et al [57] reported that silicon mitigated heavy metal stress by regulating endogenous phytohormones, silicon genes and P-type heavy metal ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [57] reported that silicon mitigated heavy metal stress by regulating endogenous phytohormones, silicon genes and P-type heavy metal ATPases. El-Okkiah et al [56] stated that Cd stress in pea plants produced anatomical abnormalities, decreasing stomatal density. In addition, Cd stress induced oxidative damage in pea plants by increasing hydrogen peroxide (H 2 O 2 ) and lipid peroxidation levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots are the primary way of entry for Cd in plants, and different metal channels and transporters play a critical role in Cd uptake from roots to their transportation in aerial plant parts [ 11 ]. Cadmium toxicity in plants causes diverse changes ranging from disruption in cell division, plant growth, photosynthetic efficiency, chlorophyll synthesis, enzyme activity, and increase in oxidative stress [ 12 , 13 , 14 ]. Cd-induced oxidative stress also causes membrane damage, disturbs electron transport, and interferes with nucleic acids (DNA) and photosynthesis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%